Blood grove - Mosley, Walter (Mosley, Walter. Easy Rawlins mystery., 2021)
After being approached by a shell-shocked Vietnam War veteran who claims to have gotten into a fight protecting a white woman from a black man, Easy embarks on an investigation that takes him from mountaintops to the desert, through South Central and into sex clubs and the homes of the fabulously wealthy, facing hippies, the mob, and old friends perhaps more dangerous than anyone else.